Surface alloy formation and interdiffusion in (√5 × √5)R27°-Yb/Al(001): a combined low-energy electron diffraction and X-ray photoelectron diffraction study - Fasel, Roman; Gierer, M.; Bludau, H.; Aebi, Philipp; Osterwalder, Jürg; Schlapbach, Louis (My University, 1997)
We have investigated the atomic structure of (√5 × √5)R27°−Yb/Al(001) by low-energy electron diffraction and angle-scanned full-hemispherical X-ray photoelectron diffraction. Quantitative agreement between the results from the two methods is obtained. We find that the Yb atoms occupy substitutional sites, thus removing every fifth surface Al atom. The residual first-layer Al atoms are displaced by more than 0.5 Å from their equilibrium position, in a way that results in a quasi-twelve-fold Al coordination for the Yb atoms. An expansion of the outermost substrate layer spacing and anomalously large vibrational amplitudes for the Al atoms of this strongly reconstructed first substrate layer are determined. Furthermore, a small fraction of Yb atoms is identified to occupy second-layer sites in otherwise unreconstructed surface patches. The comparison of the results obtained from the two techniques indicates the importance of a treatment of thermal vibrations going beyond the traditional Debye-Waller model in adsorbate X-ray photoelectron diffraction.
Keywords: aluminum; chemisorption; low energy electron diffraction (LEED); low index single crystal surfaces; metal-metal interfaces; photoelectron diffraction; surface relaxation and reconstruction; ytterbium